Incidence of left ventricular thrombus following STEMI in the modern era via multimodality imaging: A systematic review and meta-analysis - Ethan Sacoransky; Danny Yu Jia Ke; Prasham Dave; Bryce Alexander; Adham El Sherbini; Joseph Abunassar; Wael Abuzeid (International Journal of Cardiology: Heart & Vasculature, 2024)
Background: Left ventricular thrombus (LVT) is a significant complication in STEMI. Previous studies were conducted prior to modern timely percutaneous reperfusion networks. Current expert opinion suggests incidence in the current era has decreased. We conducted a systematic review and meta-analysis to better understand the incidence and diagnosis of LVT in patients with STEMI treated with timely percutaneous techniques as assessed by multimodality imaging. Methods: Cochrane, EMBASE, LILACS, and MEDLINE were searched over the last 10 years only including studies using contemporary techniques. The primary outcome was detection of LVT in patients via echocardiogram with or without contrast or Cardiac MRI (cMRI) following STEMI (both anterior and any territory) treated with PCI. Data was pooled across studies and statistical analysis was conducted via random effects model. Results: 31 studies were included. 18 studies included data on any territory STEMI, totaling 14,172 patients, and an incidence of 5.6% [95% CI 4.3–7.0]. 18 studies were included in analysis for anterior STEMI, totaling 7382 patients and incidence of 12.7% [95% CI 9.8–15.6]. Relative to cMRI as a gold standard, the sensitivity of non-contrast echocardiography to detect LVT was 58.2% [95% CI 46.6–69.2] with a specificity of 97.8% [95% CI 96.3–98.8]. Conclusions: Incidence of LVT in STEMI patients treated with contemporary timely percutaneous revascularization is in keeping with historical data and remains significant, suggesting this remains an ongoing issue for further investigation. Numerically, both cMRI and contrast echo detected more LVT compared to non-contrast echo in any-territory STEMI patients.